Modification of Ca2+-Crosslinked Sodium Alginate/Gelatin films with Propolis for an improved antimicrobial action - Homem, Natália Cândido (2020)
Problems associated with microbial resistance to antibiotics are growing due to their overuse. In this scenario, plant extracts such as the propolis extract (PE) have been considered as potential alternatives to antibiotics in the treatment of infected wounds, due to its antimicrobial properties and ability to induce tissue regeneration. To improve the long-term effectiveness of PE in wound healing, polymeric films composed of biodegradable and biocompatible polymers are being engineered as delivery vehicles. Here, sodium alginate/gelatin (SA/GN) films containing PE were prepared via a simple, green process of solvent casting/phase inversion technique, followed by crosslinking with calcium chloride (CaCl2) solutions. The minimum inhibitory concentration (MIC) of PE was established as 0.338 mg/mL for Staphylococcus aureus and 1.353 mg/mL for Pseudomonas aeruginosa, the most prevalent bacteria in infected wounds. The PE was incorporated within the polymeric films before (blended with the polymeric solution) and after (immobilization via physisorption) their production. Flexible, highly hydrated SA/GN/PE films were obtained, and their antibacterial activity was assessed via agar diffusion and killing time kinetics examinations. Data confirmed the modified films effectiveness to fight bacterial infections caused by S. aureus and P. aeruginosa and their ability to be applied in the treatment of infected wounds.